A dynamic quantitative evaluation of higher education return: evidence from Taiwan education expansion†. Issue 2 (2nd April 2016) - Kuo, Mien-Yun; Shiu, Ji-Liang
Abstract : This study analyzes the dynamics of the rate of the return to college share on wage rates, by controlling for the effects of individual schooling. Using an endogenous selection model enables controlling the labor idiosyncratic matching structure and unobserved characteristics of people and cities. A 1% increase in college share in the workforce raised the wages by approximately 0.7% for the less educated groups, and approximately 0.5% for the college-educated group. The dynamics of externalities from the share of college graduates rose from approximately 0.3% in 1998 to approximately 0.8% in 2002, and then decreased gradually to approximately 0.5%. The estimation results also show that the expanding higher education benefits female more than male.